Effect of hydromechanical forces on the production of filamentous haemagglutinin and pertussis toxin of Bordetella pertussis - Rodríguez, María Eugenia (1993)
The production of Bordetella pertussis extracytoplasmic filamentous haemagglutinin (FHA) and pertussis toxin (PT) in a bioreactor under stirring conditions was studied in order to investigate the effect of hydromechanical forces on yields of both antigens. It was shown that FHA loses its haemagglutinin activity when the power transmitted by the agitator and the aerator per unit volume increases, whereas PT production is not affected. The loss of FHA activity can be explained by the action of shear forces on the filamentous structure of this antigen.